2018
DOI: 10.1007/s10900-018-0527-8
|View full text |Cite
|
Sign up to set email alerts
|

South Asian Cardiovascular Disease & Cancer Risk: Genetics & Pathophysiology

Abstract: South Asians (SAs) are at heightened risk for cardiovascular disease as compared to other ethnic groups, facing premature and more severe coronary artery disease, and decreased insulin sensitivity. This disease burden can only be partially explained by conventional risk factors, suggesting the need for a specific cardiovascular risk profile for SAs. Current research, as explored through a comprehensive literature review, suggests the existence of population specific genetic risk factors such as lipoprotein(a),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 184 publications
(199 reference statements)
1
22
0
Order By: Relevance
“…SACs have one of the highest rates of atherosclerosis and coronary artery disease (CAD) in Canada ( 12 – 15 ). Previous epidemiological work has also shown elevated incidence, prevalence and mortality from CAD in this cohort, which is characterized by two basic features: lower age of onset and elevated severity ( 14 , 16 ). The INTERHEART study demonstrated that more than 90% of a population's attributable risk to myocardial infarctions (MIs), including that of South Asians, can be explained by 9 key risk factors including smoking, PA, intake of fruits and vegetables, alcohol, hypertension, abdominal adiposity, stress, elevated apolipoprotein B/apolipoprotein A1 (ApoB/ApoA1) ratio, and diabetes mellitus ( 17 ).…”
Section: Cvd Risk Factor Profile In South Asian Canadianssupporting
confidence: 61%
See 1 more Smart Citation
“…SACs have one of the highest rates of atherosclerosis and coronary artery disease (CAD) in Canada ( 12 – 15 ). Previous epidemiological work has also shown elevated incidence, prevalence and mortality from CAD in this cohort, which is characterized by two basic features: lower age of onset and elevated severity ( 14 , 16 ). The INTERHEART study demonstrated that more than 90% of a population's attributable risk to myocardial infarctions (MIs), including that of South Asians, can be explained by 9 key risk factors including smoking, PA, intake of fruits and vegetables, alcohol, hypertension, abdominal adiposity, stress, elevated apolipoprotein B/apolipoprotein A1 (ApoB/ApoA1) ratio, and diabetes mellitus ( 17 ).…”
Section: Cvd Risk Factor Profile In South Asian Canadianssupporting
confidence: 61%
“…This goal can only be achieved by identifying high risk groups within a population, determining barriers and facilitators to preventative behavior like PA, and implementing efficacious interventions to address these barriers and augment facilitators. Undoubtedly, the prevalence CVD in SACs is amongst the highest in Canada ( 12 , 13 , 15 , 16 ). They also suffer from a full spectrum of CVD risk factors, ranging from modifiable hypertension and diabetes ( 3 , 13 , 21 ) to non-modifiable adverse genetic profiles ( 125 , 126 ).…”
Section: Future Directionsmentioning
confidence: 99%
“…Only one-third of measured metabolic factors such as insulin resistance, dyslipidemia, and central obesity explain the excess CVD risk that SA face[ 51 ]. Novel biomarkers that may correlate with increased CVD include increased serum leptin and C-reactive protein, as well as adiponectin levels that are lower in SA compared to Caucasians despite similar BMI[ 99 ]. The correlation between decreased adiponectin and increased insulin resistance is particularly strong for SA[ 100 ].…”
Section: Individual Cardiovascular Risk Factorsmentioning
confidence: 99%
“…Lp(a) levels are largely genetically determined, varying over 1000-fold among individuals and 5-fold across populations. SA have a median Lp(a) concentration of 16 mg/dL compared to 6 mg/dL in Caucasians[ 99 ]. Elevated Lp(a) levels associate with vulnerable plaques and culprit lesions in acute coronary syndromes, including premature CAD, correlating with the extent and severity of both acute coronary syndrome, CAD, and coronary artery calcium score[ 17 ].…”
Section: Individual Cardiovascular Risk Factorsmentioning
confidence: 99%
“…One-third of the population in South Asia develops CVD during their lifetime [ 5 ], making it a major public health and clinical problem. Although considerable diversity exists between countries in South Asia, all South Asians have markedly higher risk of CVD than other ethnicities [ 3 , 6 ]. The rise in CVD might reflect the intersectionality of poor health systems, behavioral factors, genetic factors, and gender factors in South Asia.…”
mentioning
confidence: 99%